Dissecting G-Quadruplexes and I-Motifs in Cis-Regulatory Regions of Mammals and Plants: Life Sciences-Computational Biology - Renuka, Vemparala; Rajesh Yella, Venkata (International Journal of Life Science and Pharma Research, 2022)
The evolutionary constraints of a gene consist of cis-gene regulatory regions, such as promoters and enhancers, which contribute to the regulation of gene expression. Several genomic and computational studies stated the roles of G-quadruplex and i-motif structures in vital cellular processes like transcription, translation, gene regulation, etc. The formation of these non-B DNA structures is supported by the occurrence of unique repeated sequences. However, many studies lean toward understanding the role of the G-quadruplex, and only recent studies indicated i-motif significance. In this study, we attempted to dissect the enrichment of G-quadruplex and i-motifs in promoter regions of mammals and plants. To this end, we employed the genomic sequences encompassing -500 to +500 region relative to the gene start positions in mammals and plants retrieved from the UCSC browser and Plant Genome database (PlantGDB). We computed the putative G-quadruplexes and i-motifs with well-recognized regular expression sequence patterns. We observed that G-quadruplex motifs showed preponderance in mammals, algal species, namely, green algae, and Chlamydomonas when compared to plants. Contrastingly i-motifs are enriched in both monocot and dicot plants compared to G-quadruplex motifs. The comparative examinations in this study revamp our understanding of the two quadruplex structures and their emerging functional roles in complex eukaryotes.